Turkish adaptation and psychometric testing of the caring assessment tool‐administration. - İleri, Serap; Boz, İlkay; Kocaman, Gülseren (Perspectives in Psychiatric Care, 2022)
Purpose: The purpose of this study was to adapt the Caring Assessment Tool‐Administration (CAT‐Adm) to Turkish and to test the psychometric properties. Design and Methods: The study was carried out in a cross‐sectional and methodological design. The sample consisted of 578 nurses. Findings: The total score correlation coefficients of the items in the scale ranged from 0.69 to 0.90, and the Cronbach alpha reliability coefficient was 0.98, indicating excellent reliability. The results of the factor analysis confirmed the single‐factor structure of CAT‐Adm and the scale fit was good. Conculation: In this study, CAT‐Adm was determined to be a reliable and valid tool. Practice Implications: With the use of CAT‐Adm, nurses' perceptions of nurse managers' approach can be evaluated.